1998
DOI: 10.1046/j.1365-2109.1998.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the repartitioning agent ractopamine on the growth and body composition of rainbow trout, Oncorhynchus mykiss (Walbaum), fed three levels of dietary protein

Abstract: Ractopamine is a synthetic catecholamine analogue which is known to affect the growth performance of both terrestrial and aquatic livestock species when it is incorporated into their feed. To investigate the effect of ractopamine on fish, rainbow trout, Oncorhynchus mykiss (Walbaum), (initial weight = 385.2 ± 1.4 g) were fed six iso‐energetic (16.6 MJ kg−1) practical diets supplying two levels of ractopamine (0 and 10mgkg−1) at three levels of crude protein (CP; 25%, 35% and 45%) for 112 days. The mean weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Regarding fish, phenethanolamines had a more pronounced effect on performance, protein increase and fat reduction of Siluriforms (Mustin and Lovell, 1993;Mustin and Lovell, 1995;Webster et al, 1995). Moccia et al (1998) speculated that differences in responses to RAC observed between Siluriforms and Salmonids could be partly caused by differences in rearing water temperatures. However, the Cyprinid rohu reared in warm water (26-30ºC) showed growth performance, protein increment and fat reduction similar to rainbow trout.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding fish, phenethanolamines had a more pronounced effect on performance, protein increase and fat reduction of Siluriforms (Mustin and Lovell, 1993;Mustin and Lovell, 1995;Webster et al, 1995). Moccia et al (1998) speculated that differences in responses to RAC observed between Siluriforms and Salmonids could be partly caused by differences in rearing water temperatures. However, the Cyprinid rohu reared in warm water (26-30ºC) showed growth performance, protein increment and fat reduction similar to rainbow trout.…”
Section: Resultsmentioning
confidence: 99%
“…While pigs have large weight gain in the finishing phase, most of the fish in the same phase have a minimal growth rate (Johnston, 1999). Other researchers have also reported that the use of dietary ractopamine does not improve the performance of P. mesopotamicus juveniles (Bicudo et al, 2012) or other fish species such as Cyprinus carpio juveniles (Devens et al, 2012) and Oncorhynchus mykiss (Moccia et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Commercial extruded trout feed was used as the feed material according to the size of the fingerlings (No: 0-1-2-3). The doses of the growth agent added to the feeds were calculated as (0.0, 27.4, 54.8 and 82.2 µg/g) by taking the results of other studies conducted with similar purposes (McLean et al, 1997;Moccia et al, 1998; into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, 4 fingerlings randomly chosen from each of the 16 units were weighed on a ±1 mg precision digital scale, their weights were determined, their total length was measured with 0.1 cm error, and their values of head, fin, carcass weight, hepatosomatic index and viscerosomatic index were measured respectively in order to determine meat composition as described by Moccia et al (1998).…”
Section: Methodsmentioning
confidence: 99%